2014
DOI: 10.1063/1.4866774
|View full text |Cite
|
Sign up to set email alerts
|

Anomalous Hall effect in Co/Ni multilayers with perpendicular magnetic anisotropy

Abstract: Anomalous Hall effect is studied in Co/Ni multilayers with perpendicular magnetic anisotropy, which consists of ferromagnetic-ferromagnetic interfaces. The anomalous Hall coefficient of [Co/Ni]N multilayer increases with temperature. The anomalous Hall coefficient at the zero temperature limit is in the order of 0.01 μΩ cm/T and decreases with increasing the repetition N. It suggests that the Co-Ni interfacial contribution to anomalous Hall coefficient is of opposite sign to the bulk contribution. The anomalou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
12
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 40 publications
1
12
0
Order By: Relevance
“…We intentionally chose a capping layer of 5 nm of Al (which will naturally oxidize over typically 2 or 3 nm) to rule out any supplementary contribution related to the oxidation at Ni/Al interfaces in order to focus our discussion on Pt/Co and Co/Ni interfaces. It has been shown that Co/Ni exhibits a perpendicular magnetic anisotropy whose origin lies in the hybridization and spin-polarized charge transfer at Co/Ni interfaces [29][30][31][32][33]. Similar systems that have been reported to promote PMA are Co/Pt/Ni multilayers [34] and Pt/Co/Pt [35] trilayers.…”
mentioning
confidence: 91%
“…We intentionally chose a capping layer of 5 nm of Al (which will naturally oxidize over typically 2 or 3 nm) to rule out any supplementary contribution related to the oxidation at Ni/Al interfaces in order to focus our discussion on Pt/Co and Co/Ni interfaces. It has been shown that Co/Ni exhibits a perpendicular magnetic anisotropy whose origin lies in the hybridization and spin-polarized charge transfer at Co/Ni interfaces [29][30][31][32][33]. Similar systems that have been reported to promote PMA are Co/Pt/Ni multilayers [34] and Pt/Co/Pt [35] trilayers.…”
mentioning
confidence: 91%
“…For inhomogeneous granular and multilayer samples, spin-dependent interfacial scattering leads to large γ (>2), e.g., γ = 2.6 in Fe/Cr multilayers [13] and γ = 3.7 in Co-Ag granular thin films [14], which cannot be ascribed to any of the three mechanisms above. Moreover, in the multilayer heterostructures, the shunting effect is a critical issue in Hall resistivity measurement [15][16][17]. Because the Hall voltage depends on the current flow in each layer, the conventional bulk scaling law cannot be applied for samples with different current distributions.…”
Section: Introductionmentioning
confidence: 99%
“…The contributions of surface and interface scattering on AHE were also verified in ferromagnetic/nonmagnetic (FM/NM) multilayers, such as [Co/Pd] n , [Co/Cu] n and [Co/Pt] n [6][7][8]. The effect of FM/FM interface on AHE was studied in [Co/Ni] n structures [9]. The AHE in ferromagnet/semiconductor (FM/SC) structures was also reported in Fe/Si, Fe/Ge and Fe/GaAs [10][11][12].…”
Section: Introductionmentioning
confidence: 96%